The Effect of the Application of the 5E Learning Cycle Model on Mathematical Communication Skills in Junior High School Students - Susanti, Putri Aulia; Hutapea, Nahor Murani; Saragih, Sehatta (FKIP-Universitas Riau, 2021)
This research is motivated by the low students mathematical communication skills. To overcome this problem is by improving the learning process that provides opportunities for students. One of them is by applying the 5E Learning Cycle model. The 5E Learning Cycle model is a series of activities so that students can master the competencies achieved in learning by taking an active role, directed to seek and discover new knowledge themselves. The research is to investigate the impact of the application of Learning Cycle 5E on mathematical communication skills in terms of overall, ability level and, interaction between learning model and ability level. This research is a quasi-experimental study with a pretest post-test control design. The results of data analysis show that the mathematical communication skills of students who learn using the 5E learning cycle model are better than students with conventional learning. For students mathematical communication skills at the moderate level, the 5E learning cycle model is better, but not better for high and low levels. There is no interaction between the learning model and ability level of mathematical communication skills.